Anti-risk Potential of Administrative Socialization - Sergei Boresobich Murashov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In an article from the perspective of the sociology of risk, we investigate the phenomenon of socialization as a process of socialization of the risks in a particular scale business structure - the business community with a high risk-taking (corporation, company). The role of management in the formation of the socialization of preventive management of organizational factors risk-taking. The notion of «risk-based socialization» as a factor of precautionary management processes, defines the basic aims and methods of risk-oriented socialization and its internal agents and requirements for their competence.